Abdominal trauma: Assessment, surgical priorities and resuscitation strategies in emergency cases (Research, Society and Development, 2024)
This study aimed to investigate the effectiveness and feasibility of a protocol for screening and early management of abdominal trauma in emergency environments, aiming to optimize the early identification of intra-abdominal injuries, prioritize surgical interventions and resuscitation strategies, and improve outcomes. clinical outcomes and patient survival. The methodology selected to carry out this research is a narrative literature review study, where a data collection was carried out in the scientific bases: LILACS and SCIELO. The results showed that implementing an early screening and management protocol for abdominal trauma in emergency settings is a crucial strategy to improve clinical outcomes and patient survival. Recent studies have emphasized the importance of a systematic and rapid approach to the early identification of intra-abdominal injuries, prioritizing surgical interventions and resuscitation strategies. Adopting an evidence-based screening protocol demonstrated a significant reduction in the time to diagnosis of intra-abdominal injuries, resulting in lower mortality among patients with severe abdominal trauma.